Floral nectary structure, nectar presentation and morpho-anatomical analysis of male-fertile and male-sterile anthers in onion (Allium cepa, Amaryllidaceae) - González, Ana María (2023)
Fil: González, Ana María. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.